International justice: a view of western communitarianism - Chris O Abakare (Center for Humanities and Innovation Studies, 2021)
Does the communitarian perspective on politics offer a credible account of the conception of the relationship between the self and the other, which can provide a valid conceptual basis for justice among states? How does the understanding of the state as a nation-state impact the possibility of international justice? These questions constitute the primary concern of this work. It must be mentioned that although any attempt to analyze the international realm through the lens of communitarianism would necessarily entail invoking the politics of nationalism, this study deals with nationalism only to assess how communitarianism contributes to international justice. The study is not concerned with the validity or authenticity of a people's claims to nationalism; rather, the aim is to work out a communitarian perspective on international justice. This work argues that though the communitarian understanding of justice does offer a valid and credible account of the conception of the self and his relationship with the other, it fails to apply to the international context. Justice can only be required, negotiated, and implemented among members of a community. To understand international justice, what is required is the recognition of common humanity, a commonly shared conception of the good outside the boundaries of the nation-state. The communitarian perspective does not offer space for such recognition.